Aluminum–phthalocyanine chloride associated to poly(methyl vinyl ether-co-maleic anhydride) nanoparticles as a new third-generation photosensitizer for anticancer photodynamic therapy - Muehlmann LA (Dove Medical Press, 2014)
Luis Alexandre Muehlmann,* Beatriz Chiyin Ma,* João Paulo Figueiró Longo, Maria de Fátima Menezes Almeida Santos, Ricardo Bentes AzevedoDepartment of Genetics and Morphology, Institute of Biological Sciences, University of Brasília, Brasília/DF, Brazil *These authors contributed equally to this work Abstract: Photodynamic therapy is generally considered to be safer than conventional anticancer therapies, and it is effective against different kinds of cancer. However, its clinical application has been significantly limited by the hydrophobicity of photosensitizers. In this work, a system composed of the hydrophobic photosensitizer aluminum–phthalocyanine chloride (AlPc) associated with water dispersible poly(methyl vinyl ether-co-maleic anhydride) nanoparticles is described. AlPc was associated with nanoparticles produced by a method of solvent displacement. This system was analyzed for its physicochemical characteristics, and for its photodynamic activity in vitro in cancerous (murine mammary carcinoma cell lineage 4T1, and human mammary adenocarcinoma cells MCF-7) and noncancerous (murine fibroblast cell lineage NIH/3T3, and human mammary epithelial cell lineage MCF-10A) cell lines. Cell viability and the elicited mechanisms of cell death were evaluated after the application of photodynamic therapy. This system showed improved photophysical and photochemical properties in aqueous media in comparison to the free photosensitizer, and it was effective against cancerous cells in vitro. Keywords: third-generation photosensitizer, nanoparticles, cancer, photodynamic therapy, drug delivery systems